Dynamic manipulation of far-red light and temperature for the production of microgreens in controlled environments - Fulton, Oliver Wynne, author; Craver, Joshua, advisor; Bousselot, Jennifer, committee member; Johnson, Sarah, committee member (Colorado State University. Libraries, 2024)
Microgreens are becoming increasingly popular for controlled environments due to their ease of production, profitability, and high concentration of nutrients. However, to date there is little information on how light spectra and temperature interactively affect plant growth and morphology to optimize the production of horticultural crops, including microgreens. Therefore, the objective of this study was to investigate the benefit of reducing air temperature as well as supplementing with far-red (700-750 nm) photons to enhance the morphology and phytochemical concentrations of three Brassica microgreen species. Seeds of mustard (Brassica juncea 'Garnet Giant'), kohlrabi (Brassica oleracea var. gongylodes), and red cabbage (Brassica oleracea var. capitata) were sown on rockwool substrate and grown in walk-in growth chambers using ebb and flow hydroponic systems at the CSU Spur campus. Upon germination, microgreens were grown under ambient air temperature of either 18 or 21 °C and subjected to the following lighting treatments: photosynthetic photon flux density (PPFD) of 165 μmol·m−2·s−1 (PAR165); PPFD of 200 μmol·m−2·s−1 (PAR200); and PPFD of 165 μmol·m−2·s−1 + 35 μmol·m−2·s−1 of far-red light (PAR165+FR35). Expected shade avoidance responses (e.g., increased hypocotyl elongation) due to a low R:FR value occurred in all three species under PAR165+FR35, regardless of temperature. Additionally, fresh weight of red cabbage and kohlrabi was greatest under PAR165+FR35 or similar between PAR165+FR35 and PAR200, respectively, at both temperatures. While an interaction with temperature was not observed, results support the role of far-red light in the manipulation of both microgreen quality and biomass accumulation. A follow-up experiment was conducted with red cabbage microgreens grown under the previous far-red lighting treatment (PAR165+FR35) to explore the dynamic manipulation of air temperature throughout production. While production under PAR165+FR35 should result in characteristic shade avoidance responses, including a potential decrease in pigmentation, we hypothesized that a reduction in air temperature during production could serve as a secondary stressor to increase phytochemical concentrations (e.g., anthocyanins). Using the same experimental setup described for the previous experiment, red cabbage microgreens were grown at an air temperature of 21 °C for 12 days (Control) or moved 6, 8, 10, or 11 days after sowing to an air temperature of 16 °C. Shade avoidance responses (e.g., hypocotyl elongation) and both fresh and dry weight were reduced for microgreens transferred to the air temperature of 16 °C on days 6 and 10 compared to all other treatments. Interestingly, microgreens transferred to the air temperature of 16 °C resulted in greater dry weight compared to Control. While results were not significant, an anticipated trend of increased relative anthocyanin content in response to longer durations at the 16 °C air temperature was observed. Although the dynamic manipulation of both far-red light and temperature could lead to microgreens with optimal yield, morphological characteristics, and phytochemical concentrations, future research is warranted to elucidate target environmental setpoints, durations, and possible interactions.